2014
DOI: 10.1039/c4nr05436a
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the early stages of silica-controlled barium carbonate crystallisation

Abstract: Recent work has demonstrated that the dynamic interplay between silica and carbonate during co-precipitation can result in the self-assembly of unusual, highly complex crystal architectures with morphologies and textures resembling those typically displayed by biogenic minerals. These so-called biomorphs were shown to be composed of uniform elongated carbonate nanoparticles that are arranged according to a specific order over mesoscopic scales. In the present study, we have investigated the circumstances leadi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 60 publications
(284 reference statements)
4
28
0
Order By: Relevance
“…In each iteration of this cyclic process, the deposition of amorphous silica limits the barium carbonate structures to nanorods, thus preventing them from growing into larger euhedral witherite crystals. 32 Our results show that the topographic patterns form in the immediate wake of the crystallization front which is in agreement with the pH oscillation model. In addition, the stripes are parallel to the growing front suggesting a spatial synchronization of these oscillations.…”
Section: ■ Conclusionsupporting
confidence: 88%
“…In each iteration of this cyclic process, the deposition of amorphous silica limits the barium carbonate structures to nanorods, thus preventing them from growing into larger euhedral witherite crystals. 32 Our results show that the topographic patterns form in the immediate wake of the crystallization front which is in agreement with the pH oscillation model. In addition, the stripes are parallel to the growing front suggesting a spatial synchronization of these oscillations.…”
Section: ■ Conclusionsupporting
confidence: 88%
“…4 Our results add to these previous findings and suggest that Ba 2+ and SO 4 2− ions undergo association to form stable complexes prior to liquid-liquid separation and solid barium sulphate nucleation, as reported previously for other sparingly soluble minerals such as CaCO 3 (ref. 22 The formation of ion associates (pairs and/or larger clusters) prior to nucleation thus seems to be a widespread feature of many mineral precipitation processes. 22 The formation of ion associates (pairs and/or larger clusters) prior to nucleation thus seems to be a widespread feature of many mineral precipitation processes.…”
Section: Discussionmentioning
confidence: 99%
“…In these calibration runs, Ba 2+ potential was measured as a function of solution concentration, using identical settings as in the precipitation runs. 22)) and to quantitatively assess the multiple effects of additives on the early stages of nucleation and growth of such minerals. This results in a sustainable approximation.…”
Section: Titration Experimentsmentioning
confidence: 99%
“…1,23 Most probably, this behaviour is caused by the presence of silica, which may act as an efficient inhibitor for carbonate growth (thus restricting the size of the crystallites to the nanoscale) 26 and/or accelerate nucleation by lowering interfacial energies through epitaxial matching. In our opinion, this is a plausible scenario as it was shown that the bulk mother solution of biomorphs is sufficiently supersaturated throughout the entire growth process 18 and hence BaCO 3 crystallisation does actually not need a local increase in supersaturation, while this is not necessarily true for silica.…”
Section: Figmentioning
confidence: 99%